UJI AKTIVITAS ANTIOKSIDAN SENYAWA FLAVONOID PADA KULIT BATANG TUMBUHAN GAYAM (Inocarpus fagiferus Fosb.) - Hany Anastasia, Made; Rahayu Santi, Sri; Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry), 2016)
Gayam ( Inocarpus fagiferus Fosb) is a tropical plant whose stem bark has been used as traditional medicine. This research aims to identify the flavonoides isolate from stem bark of gayam and identify the class of flavonoids compound as antioxidant. Extraction of 1000 g stem bark powder with 8500 mL of 96 % ethanol to yield 30 g concentrated ethanol extract. Partition of 15 g extract ethanol-water (7:3) with chloroform and n-buthanol to yield 1,5 g concentrated chloroform extract, 5,87 g concentrated n-buthanol extract and 5,63 g concentrated water extract. The flavonoids test using Wilstatter and Bate-Smith Matcalf reagent showed that n-buthanol and water extract contain flavonoids compounds. Antioxidant activity of flavonoids tested with DPPH method and lipid peroxide ammonium thiocyanate method showed that n-buthanol extract had antioxidant activity with IC 50 of 24 ppm and n-buthanol extract has ability to inhibit the formation of lipid peroxide with inhibition value of 63,04 %. Separation of n-buthanol extract using thin layer chromatography preparative with chloroform as mobile phase and silica gel GF 254 as stationary phase obtained four fractions. Flavonoids test showed that fraction F3 contained flavonoids compounds. FTIR analysis indicated that isolate had functional groups such as  -OH , C=O, C-O alcohol, C=C aromatic, C-H aromatic and C-H aliphatic. UV-vis spectra showed 2 peaks at ? 310 nm  and  261 nm which indicated flavonoids group of  isolfavone with hydroxyl groups at C-5 and  C-7. Antioxidant activity test with DPPH method showed that the isolate had antioxidant activity with IC 50 of 1 ppm.
Keywords: Gayam, flavonoids, antioxidant